Telephone conversation re telegram from Paul Langevin (note) - Langevin, Paul, 1872-1946
021-0008-001 TELEPHONE CONVERSATION 11th March, 1937. The following TELEGRAM addressed "Committee Internationale, Friends' House" (probably intended for Transport House) was telephoned from Friends' House (in translation) "Sorry not to be in London. My heart is with you. Greet warmly delegates of the Executive Commission. Paul Langevin." Telephoned the above to Mr Bell at Central Hall. Whitehall 6341 CB.11/3/37 292/946/21/8